Nanograined surface shell wall controlled ZnO–ZnS core–shell nanofibers and their shell wall thickness dependent visible photocatalytic properties. Issue 5 (15th February 2017) - Ranjith, Kuglaur Shanmugam; Senthamizhan, Anitha; Balusamy, Brabu; Uyar, Tamer
Abstract : The core–shell form of ZnO–ZnS based heterostructural nanofibers (NF) has received increased attention for use as a photocatalyst owing to its potential for outstanding performance under visible irradiation. Abstract : The core–shell form of ZnO–ZnS based heterostructural nanofibers (NF) has received increased attention for use as a photocatalyst owing to its potential for outstanding performance under visible irradiation. One viable strategy to realize the efficient separation of photoinduced charge carriers in order to improve catalytic efficiency is to design core–shell nanostructures. But the shell wall thickness plays a vital role in effective carrier separation and lowering the recombination rate. A one dimensional (1D) form of shell wall controlled ZnO–ZnS core–shell nanofibers has been successfully prepared via electrospinning followed by a sulfidation process. The ZnS shell wall thickness can be adjusted from 5 to 50 nm with a variation in the sulfidation reaction time between 30 min and 540 min. The results indicate that the surfaces of the ZnO nanofibers were converted to a ZnS shell layer via the sulfidation process, inducing visible absorption behavior. Photoluminescence (PL) spectral analysis indicated that the introduction of a ZnS shell layer improved electron and hole separation efficiency. A strong correlation between effective charge separation and the shell wall thickness aids the catalytic behavior of the nanofiber network and improves its visible responsive nature. The comparative degradation efficiency toward methylene blue (MB) has been studied and the results showed that the ZnO–ZnS nanofibers with a shell wall thickness of ∼20 nm have 9 times higher efficiency than pristine ZnO nanofibers, which was attributed to effective charge separation and the visible response of the heterostructural nanofibers. In addition, they have been shown to have a strong effect on the degradation of Rhodamine B (Rh B) and 4-nitrophenol (4-NP), with promising reusable catalytic efficiency. The shell layer upgraded the nanofiber by acting as a protective layer, thus avoiding the photo-corrosion of ZnO during the catalytic process. A credible mechanism for the charge transfer process and a mechanism for photocatalysis supported by trapping experiments in the ZnO–ZnS heterostructural system for the degradation of an aqueous solution of MB are also explicated. Trapping experiments indicate that h + and ˙OH are the main active species in the ZnO–ZnS heterostructural catalyst, which do not effectively contribute in a bare ZnO catalytic system. Our work also highlights the stability and recyclability of the core–shell nanostructure photocatalyst and supports its potential for environmental applications. We thus anticipate that our results show broad potential in the photocatalysis domain for the design of a visible light functional and reusable core–shell nanostructured photocatalyst.